2017
DOI: 10.1101/190173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The ERA-related GTPase AtERG2 associated with mitochondria 18S RNA is essential for early embryo development inArabidopsis

Abstract: The ERA (E. coli RAS-like protein)-related GTPase (ERG) is a nuclear-encoded GTPase with two conserved domains: a GTPase domain and a K Homology domain. ERG plays a vital role in early seed development in Antirrhinum majus. However, the mechanism that regulates seed development remains unclear. Blasting the genome sequence revealed two homologies of ERG, AtERG1, and AtERG2 in Arabidopsis. In this study, we found that AtERG2 is localised in the mitochondria and binds mitochondrial 18S RNA. Promoter and transcri… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Zhang et al (2017) identified 4,192 proteins expressed differentially between fertile and sterile ovules, and most of the differential expressed proteins participated in DNA replication, active oxygen metabolism, ATP synthesis and so on. In addition, previous research had shown that abnormal metabolism of reactive oxygen species could also affect fertility of plants (Zhang et al, 2014;Cheng et al, 2018;Nie, Cheng & Hua, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2017) identified 4,192 proteins expressed differentially between fertile and sterile ovules, and most of the differential expressed proteins participated in DNA replication, active oxygen metabolism, ATP synthesis and so on. In addition, previous research had shown that abnormal metabolism of reactive oxygen species could also affect fertility of plants (Zhang et al, 2014;Cheng et al, 2018;Nie, Cheng & Hua, 2020).…”
Section: Introductionmentioning
confidence: 99%